Educational social software for context-aware learning collaborative methods and human interaction - Lambropoulos, Niki, 1966-; Romero, Margarida, 1980- (Information Science Reference, 2010)
"This book examines socio-cultural elements in educational computing focused on design and theory where learning and setting are intertwined"--Provided by publisher.